The effect of sharp-crested weir shape on air entrainment - Baylar, A; Emiroglu, ME (Natl Research Council Canada, 2002)
Aeration in the waters of rivers and streams is very important to the quality and existence of aquatic life. If the overfall jets downstream of weir structures plunges into a plunge pool, entrained air bubbles will contribute to aeration. This paper investigates sharp-crested weirs having different cross-sectional geometry and their effect on the air entrainment rate. It is demonstrated that the air entrainment rate of a 30degrees triangular sharp-crested weir is better than that of the other sharp-crested weirs tested. Moreover, variation in the number of V-notches over the width of the weir plate was studied for 30degrees triangular sharp-crested weirs. The 30degrees triangular sharp-crested weir with two V-notches was found to have higher values of air entrainment rate.
Keywords: aeration; air entrainment rate; plunging overfall jet; sharp-crested weir